Prospective comparison between magnetic resonance imaging and computed tomography in colorectal cancer staging. Issue 6 (13th August 2017) - Koh, Frederick H. X.; Tan, Ker‐Kan; Teo, Lynette L. S.; Ang, Bertrand W. L.; Thian, Yee‐Liang
Abstract : Background: Diffusion‐weighted (DW) imaging is a functional magnetic resonance imaging (MRI) technique that detects lesions with high cellularity, such as malignant tumours. This prospective study was performed to compare the accuracy of DW‐MRI with multidetector computed tomography (MDCT) in staging of colorectal cancer. Methods: Thirty patients with histologically proven colorectal cancer were prospectively recruited. Each patient underwent both MDCT and DW‐MRI of the abdomen–pelvis for primary staging. Images were evaluated for nodal and distant metastases. The reference standard was histopathological findings for nodal involvement and surveillance imaging for suspected hepatic metastases. Results: The primary cancers were located in the rectum ( n = 16, 53.3%), sigmoid colon ( n = 9, 30%) and right colon ( n = 5, 16.6%). For nodal metastases, the sensitivity and specificity of DW‐MRI were 84.6% (95% confidence interval (CI): 54.6–98.1%) and 20.0% (95% CI: 2.5–55.6%) compared with 84.6% (95% CI: 54.6–98.1%) and 40.0% (95% CI: 12.2–73.8%) for MDCT. For liver metastases, the sensitivity and specificity for DW‐MRI were 100.0% (95% CI: 63.1–100.0%) and 100% (95% CI: 84.6–100%) compared with 87.5% (95% CI: 47.4–99.7%) and 95.5% (95% CI: 77.2–99.9%) for MDCT. DW imaging altered the clinical management in three (10.0%) patients by detecting missed hepatic metastases in two patients and accurately diagnosing another patient with a hepatic cyst, mistaken for metastasis on MDCT. Conclusion: DW‐MRI is more accurate for detecting hepatic metastases in colorectal cancer compared with MDCT.